Expression and significance of lncRNAs derived from PBMC in rheumatoid arthritis - Yang, Xiaoke; Yang, Zhongling; Shuai, Ziqiang; Zhang, Mingming; Xu, Sheng-qian; Shuai, Zong Wen (Frontiers in Immunology, 2025)
BackgroundLong non-coding RNAs (lncRNAs) are gaining recognition for their critical involvement in diverse autoimmune disorders. Nevertheless, reseach investigating the role of lncRNAs in rheumatoid arthritis (RA) is relatively scarce.MethodsComprehensive transcriptome sequencing was executed to acquire a lncRNA expression pattern in peripheral blood mononuclear cells (PBMC) of RA. Then, we confirmed the sequencing data by real-time quantitative polymerase chain reaction (RT-qPCR).ResultsThe findings showed decreased levels of LINC00494, TSP0AP1-AS1, MCM3AP-AS1 and LINC01588, increased levels of OIP5-AS1, in PBMC of RA compared to controls. ROC analysis for the five dysregulated lncRNAs demonstrated an area under curve (AUC) extending from 0.654 to 0.915, and their combination had high utility for accurate RA diagnosis (AUC = 0.920). There existed a negative relation between RF and LINC00494 expression (P=0.027), positive relation between anti-CCP and MCM3AP-AS1 (P=0.024), and negative relation between CRP and LINC01588 expression (P=0.020).ConclusionsOur study indicated that LINC00494, TSP0AP1-AS1, MCM3AP-AS1, LINC01588 and OIP5-AS1 in PBMC may be the biomarkers for RA.